Too much for human endurance : the George Spangler farm hospitals and the Battle of Gettysburg - Kirkwood, Ronald D. (Savas Beatie, 2019)
The stories of the doctors, nurses and patients at the Union Army's hospital in Gettysburg come to life in this unique Civil War history. Those who toiled and suffered at the Army of the Potomac's XI Corps hospital at the George Spangler Farm in Gettysburg have long since departed. But Ronald D. Kirkwood, a journalist and George Spangler Farm expert, shares their stories'many of which have never been told before'in this gripping and scholarly narrative. Using a wealth of firsthand accounts, Kirkwood re-creates the XI Corps hospital complex and its people'especially George and Elizabeth Spangler, whose farm was nearly destroyed in the fateful summer of 1863. A host of notables make appearances, including Union officers George G. Meade, Henry J. Hunt, Edward E. Cross, Francis Barlow, Francis Mahler, Freeman McGilvery, and Samuel K. Zook. Pvt. George Nixon III, great-grandfather of President Richard M. Nixon, would die there, as would Confederate Gen. Lewis A. Armistead, who fell mortally wounded at the height of Pickett's Charge. Kirkwood presents the most complete lists ever published of the dead, wounded, and surgeons at the Spanglers' XI Corps hospital, and breaks new ground with stories of the First Division, II Corps hospital at the Spanglers' Granite Schoolhouse. He also examines the strategic importance of the property itself, which was used as a staging area to get artillery and infantry to the embattled front line.